Review of the genus Nesomalium Steel, 1964 (Coleoptera, Staphylinidae, Omaliinae), with description of two new species from Ewing and Chatham islands - Shavrin, Alexey V.; Hlaváč, Peter (Zootaxa, 2023)
The New Zealand genus Nesomalium Steel, 1964 (Omaliini) with six species is reviewed and redescribed, and briefly compared with related genera. All species are redescribed and illustrated, including two new species: N. marrisi sp. n. from Chatham Island and N. lescheni sp. n. from Ewing Island (Auckland islands). Lectotypes are designated for Omalium insulare Kiesenwetter, 1877 and O. pacificum Kiesenwetter, 1877. The key to species is provided. Nesomalium insulare (Kiesenwetter, 1877) is recorded from Adams and Ewing islands for the first time.